Pharmacological and analytical aspects of gymnemic acid: A concise report - Patel K.; Gadewar M.; Tripathi R. (My University, 2025)
Gymnemic acid is the main phytoconstituents of Gymnema sylvestre (Asclepiadaceae) found in the different parts of world. Gymnemic acid posseses different pharmacological activities including supression of taste sensitivity to sweetness, showed inhibition of intestinal glucose absorption and lower the plasma glucose levels. Various techniques have been used for the isolation and characterization of the gymnemic acid so far. In the present review data was collected in regards with pharmacological activity, analytical techniques and bioavailability of gymnemic acid. This review will be helpful to the researcher in regards to the exploration of the valuable potential of the gymnemic acid. © 2012 Asian Pacific Tropical Medicine Press.